MENINGKATKAN DAYA TARIK DAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS VII MELALUI HANDS ON ACTIVITIES PADA MATERI BANGUN DATAR DI SMP NEGERI 2 KEMRANJEN, KABUPATEN BANYUMAS - Neni, Sri (Sainteks, 2010)
The purpose of this study is to show how hands on activities can increase the students’ interest, participations, and achievements in mathematics. A classroom action research through three cycles was used to achieve the purpose. The data was analyzed using triangulation, namely the matrix analysis among the three cycles and spearman and partial-based-statistics of Kendall. This technique was used to show the correlation among the variables of study. The students’ interest in mathematics, based on the analysis, was proved increasing from 40.33% to 43.03%; participations in the subject increasing from 80% to 100%; and achievements increasing from the score of 40.19 to 58.11, or from 4.5 to 5.76, or reaching 73.33%. Statistically, the analysis showed that hands on activities could increase the students’ confidence in mathematics, approximately 95%. The result significantly proves that learning mathematics through hands on activities can increase the student’s interest, activities, and achievements in the subject. Key words: Hands on activities, interest, participations, achievements.